Development of Upright Computed Tomography With Area Detector for Whole-Body Scans: Phantom Study, Efficacy on Workflow, Effect of Gravity on Human Body, and Potential Clinical Impact - Jinzaki, Masahiro (Invest Radiol, 2020)
OBJECTIVES: Multiple human systems are greatly affected by gravity, and many disease symptoms are altered by posture. However, the overall anatomical structure and pathophysiology of the human body while standing has not been thoroughly analyzed due to the limitations of various upright imaging modalities, such as low spatial resolution, low contrast resolution, limited scan range, or long examination time. Recently, we developed an upright computed tomography (CT), which enables whole-torso cross-sectional scanning with 3-dimensional acquisition within 15 seconds. The purpose of this study was to evaluate the performance, workflow efficacy, effects of gravity on a large circulation system and the pelvic floor, and potential clinical impact of upright CT. MATERIALS AND METHODS: We compared noise characteristics, spatial resolution, and CT numbers in a phantom between supine and upright CT. Thirty-two asymptomatic volunteers (48.4 ± 11.5 years) prospectively underwent both CT examinations with the same scanning protocols on the same day. We conducted a questionnaire survey among these volunteers who underwent the upright CT examination to determine their opinions regarding the stability of using the pole throughout the acquisition (closed question), as well as safety and comfortability throughout each examination (both used 5-point scales). The total access time (sum of entry time and exit time) and gravity effects on a large circulation system and the pelvic floor were evaluated using the Wilcoxon signed-rank test and the Mann-Whitney U test. For a large circulation system, the areas of the vena cava and aorta were evaluated at 3 points (superior vena cava or ascending aorta, at the level of the diaphragm, and inferior vena cava or abdominal aorta). For the pelvic floor, distances were evaluated from the bladder neck to the pubococcygeal line and the anorectal junction to the pubococcygeal line. We also examined the usefulness of the upright CT in patients with functional diseases of spondylolisthesis, pelvic floor prolapse, and inguinal hernia. RESULTS: Noise characteristics, spatial resolution, and CT numbers on upright CT were comparable to those of supine CT. In the volunteer study, all volunteers answered yes regarding the stability of using the pole, and most reported feeling safe (average rating of 4.2) and comfortable (average rating of 3.8) throughout the upright CT examination. The total access time for the upright CT was significantly reduced by 56% in comparison with that of supine CT (upright: 41 ± 9 seconds vs supine: 91 ± 15 seconds, P < 0.001). In the upright position, the area of superior vena cava was 80% smaller than that of the supine position (upright: 39.9 ± 17.4 mm(2) vs supine: 195.4 ± 52.2 mm(2), P < 0.001), the area at the level of the diaphragm was similar (upright: 428.3 ± 87.9 mm(2) vs supine: 426.1 ± 82.0 mm(2), P = 0.866), and the area of inferior vena cava was 37% larger (upright: 346.6 ± 96.9 mm(2) vs supine: 252.5 ± 93.1 mm(2), P < 0.001), whereas the areas of aortas did not significantly differ among the 3 levels. The bladder neck and anorectal junction significantly descended (9.4 ± 6.0 mm and 8.0 ± 5.6 mm, respectively, both P < 0.001) in the standing position, relative to their levels in the supine position. This tendency of the bladder neck to descend was more prominent in women than in men (12.2 ± 5.2 mm in women vs 6.7 ± 5.6 mm in men, P = 0.006). In 3 patients, upright CT revealed lumbar foraminal stenosis, bladder prolapse, and inguinal hernia; moreover, it clarified the grade or clinical significance of the disease in a manner that was not apparent on conventional CT. CONCLUSIONS: Upright CT was comparable to supine CT in physical characteristics, and it significantly reduced the access time for examination. Upright CT was useful in clarifying the effect of gravity on the human body: gravity differentially affected the volume and shape of the vena cava, depending on body position. The pelvic floor descended significantly in the standing position, compared with its location in the supine position, and the descent of the bladder neck was more prominent in women than in men. Upright CT could potentially aid in objective diagnosis and determination of the grade or clinical significance of common functional diseases.